2023
DOI: 10.3390/nu15132847
|View full text |Cite
|
Sign up to set email alerts
|

Does Vitamin Supplementation Play a Role in Chronic Kidney Disease?

Aleksandra Beata Juszczak,
Maciej Kupczak,
Tomasz Konecki

Abstract: Although the role of vitamins in the human body is proven, guidelines for patients with chronic kidney disease (CKD) remain unclear. This narrative review summarizes the findings of 98 studies of CKD and the effects of vitamin D, B, C, A, E, and K supplementation on patients on dialysis for CKD, with the aim of summarizing the existing guidelines. The findings are promising, showing the potential effectiveness of vitamin supplementation with, for example, vitamins B, D, or C. However, recommendations are still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…For example, high intakes of SFA and TFA are associated with pro-inflammatory markers and muscle mass 52 , 53 . Conversely, nutrients such as beta-carotene and vitamin C possess anti-inflammatory and muscle-building properties 54 56 . Although these nutrients were consumed around the recommended dietary allowance (RDA), research has indicated that patients experienced better outcomes when supplemented with nutrients 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, high intakes of SFA and TFA are associated with pro-inflammatory markers and muscle mass 52 , 53 . Conversely, nutrients such as beta-carotene and vitamin C possess anti-inflammatory and muscle-building properties 54 56 . Although these nutrients were consumed around the recommended dietary allowance (RDA), research has indicated that patients experienced better outcomes when supplemented with nutrients 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Another area of VitD and VitK cooperation is inflammation, since both vitamins are known to decrease the production of certain proinflammatory cytokines [ 57 ]. Thus, VitK increases vitamin D’s beneficial effect on bone mineralization [ 57 ], as was shown in some clinical trials, as reviewed elsewhere [ 60 , 63 ]. Interestingly, it was even suggested that for osteoporosis treatment, not only VitD plus Ca but also additional supplementation with VK2 plus the amino acid taurine might be recommended [ 59 ].…”
Section: Vitamin Kmentioning
confidence: 99%
“…The PIVKA levels usually increase in the case of VitK deficiency [ 64 ]. Undercarboxylated coagulation factor II, referred to as “Protein Induced by Vitamin K Antagonism or Absence II” (PIVKA-II), is a less commonly used but potentially very accurate marker, reflecting the hepatic VitK status [ 54 , 63 ]. The inactive form of the calcification inhibitor MGP, i.e., dephosphorylated undercarboxylated MGP, and undercarboxylated OC can be used as biomarkers of an extra-hepatic VitK status [ 54 ].…”
Section: Vitamin Kmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, vitamin D sufficiency reduces not only acute infections like SARS-CoV-2 but also the risks of chronic infections, such as tuberculosis. Sufficient generation of calcitriol within the immune cells regulates innate and adaptive immunity, potentiating the innate response (monocytes/macrophages with anti-microbial activity) [10][11][12][13]71]. Calcitriol also modulates B lymphocytes and plasma cells for immunoglobulin production and stabilizes B-cells [61,72], increasing anti-microbial peptide synthesis (Sections 3.5 and 3.6).…”
Section: Vitamin D Activates Immune Cellsmentioning
confidence: 99%